THE CONCEPT OF AMÂNAH IN INFORMED CONSENT - Zulham Zulham (AHKAM : Jurnal Ilmu Syariah, 2014)
The Concept of Amânah in Informed Consent. The Appeal Decision of the Supreme Court of the Republic of Indonesia Number 365K/Pid/2012 granted the appeal request of Public Prosecutor of Manado State Public Prosecutor’s Office. The Supreme Court annulled the Manado State Court Decision that imposed 10 (ten) months criminal imprisonment to each defendant. The Indonesian Doctors Association argued that the contract between doctor and patient is a contract of process, not a contract of result. At the very least, this Appeal Decision provided an opportunity for legal experts to test and evaluate the concept of informed consent both philosophically and juridically. This paper argues that informed consent should be built on the framework of amânah which is an important concept in Islamic law.DOI: 10.15408/ajis.v14i1.1240